Pengaruh Kompetensi, Lingkungan Keluarga Dan Keberanian Mengambil Resiko Terhadap Minat Berwirausaha (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang 2018) - Devi Febriana; Pardiman Pardiman; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine the effect of Competence, Family Environment and Courage to Take Risks on Entrepreneurial Interest of Students of the Faculty of Economics and Business, Islamic University of Malang 2018. The sample used in this study was 91 students. The data analysis method used in this research is quantitative data analysis using multiple linear regression analysis. Testing the data used is simultaneous hypothesis testing (F) and partial hypothesis testing (t). The results showed that together (Test F) the Competence Variables, Family Environment and Courage to Take Risks had a positive and significant effect on the interest in entrepreneurship and based on the partial test results (T-test) the Competence variable had no effect on the interest in entrepreneurship, the Family Environment variable does not affect the interest in entrepreneurship and the variable Courage to take risks affects the interest in entrepreneurship. Keywords: Competence, Family Environment, and Courage to take risk